2015
DOI: 10.1111/1750-3841.13107
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Scale Cucumber Fermentations Brined with Calcium Chloride Instead of Sodium Chloride

Abstract: Development of low salt cucumber fermentation processes present opportunities to reduce the amount of sodium chloride (NaCl) that reaches fresh water streams from industrial activities. The objective of this research was to translate cucumber fermentation brined with calcium chloride (CaCl2 ) instead of NaCl to commercial scale production. Although CaCl2 brined cucumber fermentations were stable in laboratory experiments, commercial scale trials using 6440 L open-top tanks rapidly underwent secondary cucumber … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(42 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Higher pasteurization temperatures and longer processes have been previously correlated with softer finished product [36]. Despite the overall reduction in mesocarp firmness in the finished products, the cucumber pickles fermented in NaCl brine were still significantly firmer than those fermented with the CaCl 2 process by 1.6 N. Instrumental mesocarp firmness values are well correlated with sensorial measurements of firmness, crispness, hardness, and crunchiness [3,19,20,37,38]. Wilson et al [15] found significant differences in hedonic texture liking for hamburger dill chips produced from cucumbers preserved by NaCl and CaCl 2 fermentation processes that were 1.1 N different in instrumental firmness values.…”
Section: Texture Qualitymentioning
confidence: 72%
See 4 more Smart Citations
“…Higher pasteurization temperatures and longer processes have been previously correlated with softer finished product [36]. Despite the overall reduction in mesocarp firmness in the finished products, the cucumber pickles fermented in NaCl brine were still significantly firmer than those fermented with the CaCl 2 process by 1.6 N. Instrumental mesocarp firmness values are well correlated with sensorial measurements of firmness, crispness, hardness, and crunchiness [3,19,20,37,38]. Wilson et al [15] found significant differences in hedonic texture liking for hamburger dill chips produced from cucumbers preserved by NaCl and CaCl 2 fermentation processes that were 1.1 N different in instrumental firmness values.…”
Section: Texture Qualitymentioning
confidence: 72%
“…In the laboratory development of the process, mesocarp firmness of cucumbers fermented in this CaCl 2 brine was found to be consistently comparable to the cucumbers fermented in a commercial brine formulation [4]. In contrast, cucumbers fermented in 12,500 L open-top tanks with the postcommercialization formulation changes showed variability in mesocarp firmness values as well as lower sensory hardness, fracturability, crispness, and crunchiness scores in some pickle products fermented and stored in CaCl 2 brines [3]. Consumer testing also showed a decreased texture liking for cucumber pickles commercially produced with the CaCl 2 brining process in some, but not all, experiments [15].…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations